Students' Critical Thinking and Writing Skills in Project-Based Learning - Suteja Suteja; Dadan Setiawan (International Journal of Educational Qualitative Quantitative Research, 2022)
This study describes the relationship between elementary school students' critical thinking and writing skills. The main objective of this research is to describe students' writing and critical thinking skills through project-based learning models. This study uses a quantitative approach with a quasi-experimental type. The research design used was a nonequivalent pretest-posttest control group design. The sample of this study was 50 students who were divided into 25 experimental groups and 25 students in the control class. This research selects 6th-grade students from one school in Bandung. The data collection instrument in this study used a description test to determine students' critical thinking and an assignment test to make persuasive texts to assess students' writing skills. The ANOVA test was used to determine the relationship between critical thinking and students' writing skills. The T-test was used to determine the differences in students' ability to write persuasive texts before and after receiving treatment with the project-based learning model. The results showed a good correlation between critical thinking and students' writing skills. In addition, there is a significant difference in students' writing skills before and after learning using the project-based learning model. It can be seen from the significance value of 0.00 <0.05. Thus the project-based learning model has a positive impact on improving students' critical thinking in learning to write and writing skills for elementary school students.